Digital Technology-Based Educational Innovation at Percut Sei Tuan State Junior High School 4 - Anggi Sofiana Nasution; Nasrul Syakur Chaniago (International Journal of Education, Language, and Social Science, 2026)
Digital technology-based educational innovation has become an important strategy for improving learning quality in the era of digital transformation. This study aims to analyze the implementation of digital technology-based educational innovation at Percut Sei Tuan State Junior High School 4, with a focus on the optimization of technology use, teacher and school readiness, and the role of school leadership in supporting digital-based learning. This research employed a qualitative approach with a phenomenological design. Data were collected through interviews, observations, and documentation involving school principals, teachers, administrative staff, and students who were directly engaged in digital learning practices. The data were analyzed through data reduction, data display, and conclusion drawing. The findings show that digital technology has been used in learning and school administration through laptops, projectors, smart TVs/interactive flat panels, Canva, Google Forms, digital attendance systems, and digital report card systems. These technologies support more interactive, effective, and student-centered learning. However, implementation remains constrained by limited facilities, unequal teacher digital competence, and the need for continuous training. The study concludes that successful digital technology-based educational innovation depends on the integration of adequate infrastructure, teacher readiness, institutional support, and adaptive school leadership.